Comparative Study of the Efficacy of Alfuzosin and Silodosin in the Medical Expulsion Therapy for Distal Ureteral Calculus: - Ansari, Imran; Agrawal, Chandra Shekhar; Thakur, Deepak K.; Khan, Sajjad Ahmed (Birat Journal of Health Sciences, 2025)
Introduction: Ureteral stones often require pharmacological intervention to aid their passage. Alpha-blockers like Alfuzosin and Silodosin are frequently used to relax ureteral smooth muscle and facilitate stone expulsion. Objectives: The objective of this study was to compare the efficacy of 10 mg Alfuzosin and 8 mg Silodosin in facilitating the passage of small ureteral stones (≤10 mm), with a focus on stone expulsion time. Methodology: The study was conducted at Birat Medical College Teaching Hospital, Nepal from December 25, 2023, to June 24, 2024. A total of 116 patients, aged 18 to 50, with unilateral, uncomplicated stones in the middle or lower ureter, were randomly assigned to receive either 10 mg Alfuzosin (Group A) or 8 mg Silodosin (Group B). Patients were monitored weekly for three weeks, and stone passage was tracked. If the stone was not passed by day 21, treatment was considered a failure. Results: The mean age of patients was 37.5 years in both groups. In Group A, 48 out of 58 patients (82.8%) passed their stones, while in Group B, 53 out of 58 patients (91.4%) succeeded in passing their stones. The difference in success rates was not statistically significant (p = 0.166). However, Silodosin led to faster stone expulsion compared to Alfuzosin. Conclusion: Both Alfuzosin and Silodosin were effective in promoting stone passage, with success rates of 82.8% and 91.4%, respectively. While Silodosin showed a higher success rate, the difference was not statistically significant. Silodosin also appeared to facilitate faster stone expulsion, suggesting it may be a slightly more effective option for stone management.